Restorative justice in Settlement of Criminal Action of Grievant Delicion - Nugraha Nugraha; Sukarmi Sukarmi (Universitas Islam Sultan Agung, 2021)
The objectives of this research are: To find out and analyze Restorative justice in the criminal law system in Indonesia. To find out and analyze the implementation of Restorative justice in the settlement of criminal complaints offenses. To find out and analyze the constraints on the implementation of Restorative justice in the settlement of criminal offenses complaints and their solutions.The method used by researchers isjuridical empirical legal approach and the specification in this research is including analytical descriptive. Based on the results of that research Restorative justice in the criminal law system in Indonesia, namely focusing on the needs of both victims and perpetrators of crimes. In addition, the Restorative justice approach helps criminals to avoid other crimes in the future. The implementation of Restorative justice in the settlement of criminal cases of complaint offenses at the Cirebon City Police using a retributive approach (retaliation) can shift to a restorative approach (recovery). The obstacle: The investigative authority granted by the Criminal Procedure Code. In the Criminal Procedure Code, investigators are given the authority to stop an investigation on the basis of the consideration that it is not a criminal act, insufficient evidence as a criminal act, and for the sake of the law. KUHAP regulates the withdrawal of reports or complaints only for certain cases, namely those which constitute offenses for complaints. The solution: In accordance with social jurispurdence theory. Propose to the highest leadership to formulate definite rules or organizational mission and the purpose of establishing a system (legalization) for the application of Restorative justice. Outreach to the community.